SWI/SNF-deficient undifferentiated/rhabdoid carcinoma of the gallbladder carrying a POLE mutation in a 30-year-old woman: a case report - Tiemo S. Gerber; Abbas Agaimy; Arndt Hartmann; Michael Habekost; Wilfried Roth; Albrecht Stenzinger; Peter Schirmacher; Beate K. Straub (BMC, 2021)
Abstract Background Undifferentiated carcinoma of the biliary tract are highly aggressive malignancies. In other organs, a subgroup of undifferentiated carcinoma related to SWI/SNF complex-deficiency have been described. Case presentation A 30-year-old woman presented with rising inflammatory markers (C-reactive protein (CRP)). Ultrasound examination revealed a large tumor of the liver. A computed tomography scan was performed and was primarily interpreted as a tumor-forming liver abscess, possibly caused by gallbladder perforation. Subsequent liver segment resection was performed. Microscopic examination showed an undifferentiated carcinoma with rhabdoid morphology and prominent inflammatory infiltrate in the gallbladder base. With SWI/SNF immunohistochemistry, intact expression of SMARCB1, SMARCA4, ARID1A, but loss of SMARCA2 and PBRM1 was detected. Next-generation-sequencing detected KRAS, PBRM1 and ARID1B mutations, a deleterious splice-site mutation in the POLE-gene and a mutation in the TP53-gene. Conclusions We were able to demonstrate loss of SMARCA2 expression and mutations characteristic of an SWI/SNF-deficient carcinoma in a tumor derived from the gallbladder. This is the first reported case of an undifferentiated carcinoma with rhabdoid features in the gallbladder carrying a POLE mutation and SWI/SNF-deficiency of PBRM1 and SMARCA2.